New Zealand landscape. Behind the scene - Migoń, Piotr (Geologos, 2019)
Book review: New Zealand landscape. Behind the scene, by Paul Williams, 2017. Elsevier, Amster-dam. 470 pages. Paperback: price $150, ISBN 978-0-12-812493-2. E-book: price $150, ISBN 978-0-12-812565-6.